Potential cost‐effectiveness of supervised injection facilities in Toronto and Ottawa, Canada. (30th November 2015) - Enns, Eva A.; Zaric, Gregory S.; Strike, Carol J.; Jairam, Jennifer A.; Kolla, Gillian; Bayoumi, Ahmed M.
Abstract: Background and Aims: Supervised injection facilities (legally sanctioned spaces for supervised consumption of illicitly obtained drugs) are controversial public health interventions. We determined the optimal number of facilities in two Canadian cities using health economic methods. Design: Dynamic compartmental model of HIV and hepatitis C transmission through sexual contact and sharing of drug use equipment. Setting: Toronto and Ottawa, Canada. Participants: Simulated population of each city. Interventions: Zero to five supervised injection facilities. Measurements: Direct health‐care costs and quality‐adjusted life‐years (QALYs) over 20 years, discounted at 5% per year; incremental cost‐effectiveness ratios. Findings: In Toronto, one facility cost 4.1 million and resulted in a gain of 385 QALYs over 20 years, for an incremental cost‐effectiveness ratio (ICER) of 10 763 per QALY [95% credible interval (95CrI): cost‐saving to 278 311]. Establishing one facility in Ottawa had an ICER of 6127 per QALY (95CrI: cost‐saving to 179 272). At a 50 000 per QALY threshold, three facilities would be cost‐effective in Toronto and two in Ottawa. The probability that establishing three, four, or five facilities in Toronto was cost‐effective was 17, 21, and 41%, respectively. Establishing one, two, or three facilities in Ottawa was cost‐effective with 13, 35, and 41% probability, respectively. Establishing no facility was unlikely to be the most cost‐effective option (14% in Toronto and 10% in Ottawa). In both cities, results were robust if the reduction in needle‐sharing among clients of the facilities was at least 50% and fixed operating costs were less than 2.0 million. Conclusions: Using a 50 000 per quality‐adjusted life‐years threshold for cost‐effectiveness, it is likely to be cost‐effective to establish at least three legally sanctioned spaces for supervised injection of illicitly obtained drugs in Toronto, Canada and two in Ottawa, Canada.